ANALISIS BEBAN KERJA TENAGA FARMASI DI INSTALASI FARMASI RUMAH SAKIT ISLAM GONDANGLEGI KABUPATEN MALANG : (Studi Kasus pada Rumah Sakit Islam Gondanglegi Tahun 2019-2021) - Fithriyah Amaliy, Faizah (Jurnal Administrasi Publik, 2024)
Workload refers to the number, of tasks and responsibilities that must be performed. This research aims to understand, evaluate, optimize, and identify. The calculation of manpower requirements was carried out by entering primary and secondary data into the WISN formula. The calculation of pharmaceutical personnel needs includes managerial services, prescription review, drug history, therapy monitoring, and information provision. This research is a descriptive study using observation and interview methods as well as monthly and annual reports. The results of this study were found in pharmacists as many as 6 people, 30 TTK, 1 person, and 4 warehouse TTK, while the total number of pharmacy workers was 25 people so the workload carried out did not match the performance of pharmaceutical officers. This is concluded by evaluating the intensity of tasks received by each pharmacy worker, managing drug stocks, providing education, conducting administration and recording, and additional roles. Management needs to ensure that they have sufficient support and efficient systems to carry out their duties and provide quality services.